Factors Shaping efl Preservice Teachers’ Identity Configuration (2019)
Preservice efl teachers face many challenges when developing their practicum. Such an experience shapes their identity and influences the teaching and learning processes. This descriptive case study is about preservice teachers’ identity formation and the factors that shaped their identity configurations during a practicum course offered at a state university in Colombia. Data, collected through interviews, reflective journals, and drawing-derived metaphors were analyzed using thematic analysis. The results identified participants’ value/belief system, personality traits, context, pedagogical decisions, reflective practice, and critical incidents as influential factors in their identity formation process. The findings also revealed that identity can be constructed through the intersection between the different experiences they go through during their practicum and their past and future trajectories. The study suggests that efl teacher education programs should take explicit pedagogical actions to incorporate the identified factors in their curriculum. This could strengthen efl preservice teachers’ identity configurations and prepare them better for their future teaching roles.